The Relationship Between Attentional Capture by Speech and Nonfluent Speech Under Delayed Auditory Feedback: A Pilot Examination of a Dual-Task Using Auditory or Tactile Stimulation - Ishida, Osamu; Iimura, Daichi; Miyamoto, Shoko (Frontiers in Human Neuroscience, 2020)
Delayed auditory feedback (DAF) leads to nonfluent speech where the voice of a speaker is heard after a delay. Previous studies suggested the involvement of attention to auditory feedback in speech disfluency. To date, there are no studies that have revealed the relationship between attention and nonfluent speech by controlling the attention allocation to delayed own voice. This study examined these issues under three conditions: a single task where the subject was asked to read aloud under DAF (single DAF task), dual task where the subject was asked to read aloud while reacting to pure tone (auditory DAF task), and dual task where the subject was asked to read aloud while reacting to vibration of their finger (tactile DAF task). The subjects also performed the single and dual tasks (auditory/tactile) under nonaltered auditory feedback where no delayed voices were involved. Results showed that the nonfluency rate under the auditory DAF task was significantly greater than that under the single DAF task. In contrast, the nonfluency rate under the tactile DAF task was significantly lower compared with that of the single DAF task. Speech became nonfluent when attention was captured by the same modality stimulus, i.e., auditory tone. In contrast, speech became fluent when attention was allocated to the stimulus that is irreverent to auditory modality, i.e., tactile vibration. This indicates that nonfluent speech under DAF is involved in attention capture owing to delayed own voice.